Occurrence of trimethyl phosphate and triethyl phosphate in a municipal wastewater treatment plant and human urine. Issue 1 (31st December 2022) - Lai, Yu-Jian; Wang, Xiao-Wei; Liu, Jing-Fu
ABSTRACT: Trimethyl phosphate (TMP) and triethyl phosphate (TEP) are extensively used as flame retardants, but their analytical methods are scarce. In this study, a robust method for both TMP and TEP in environmental water and human urine was developed by coupling of solid phase extraction (SPE) with liquid chromatography-tandem mass spectrometry (LC-MS/MS). For both TMP and TEP, the method showed good recoveries (>81%) and precisions (RSD < 5%), as well as a limit of quantification of 3 ng/L for water and 40 ng/L for urine samples, respectively. Through this method, the occurrence of TMP and TEP in municipal wastewater treatment plant (WWTP) were profiled and the anoxic step was found as the key role for their removal. Furthermore, TEP (110-2470 ng/L) was detected in all urine samples with generally higher concentration than TMP (70–2330 ng/L), which agreed with their occurrence profiles in the influent and effluent of the WWTP.